2016
DOI: 10.1021/acs.chemmater.6b02796
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Techniques for the Study of Thin Film Heterogeneous Water Oxidation Electrocatalysts

Abstract: Heterogeneous electrocatalysts for the oxygen evolution reaction (OER) are complicated materials with dynamic structures. They can exhibit potential-induced phase transitions, potential-dependent electronic properties, variable oxidation and protonation states, and disordered local/surface phases. These properties make understanding the OER, and ultimately designing higher efficiency catalysts, challenging. We report a series of procedures and measurement techniques that we have adopted or developed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
409
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(447 citation statements)
references
References 111 publications
13
409
0
1
Order By: Relevance
“…The ECSA‐normalized current density of the HEP catalyst is fully 1.3‐times and 1.8‐times higher than those of reference Ni–Fe catalyst and HEL Ni–Fe–Ba catalyst, respectively, at 1.7 V versus RHE (Figure S9, Table S3, Supporting Information). The activation energy (Figure d) and turnover frequency (TOF, Figure S10 and Table S4, Supporting Information) confirm the same trend: the HEP catalyst exhibits the lowest activation energy of 64 kJ mol −1 and the highest TOF of 0.3 s −1 .…”
supporting
confidence: 60%
“…The ECSA‐normalized current density of the HEP catalyst is fully 1.3‐times and 1.8‐times higher than those of reference Ni–Fe catalyst and HEL Ni–Fe–Ba catalyst, respectively, at 1.7 V versus RHE (Figure S9, Table S3, Supporting Information). The activation energy (Figure d) and turnover frequency (TOF, Figure S10 and Table S4, Supporting Information) confirm the same trend: the HEP catalyst exhibits the lowest activation energy of 64 kJ mol −1 and the highest TOF of 0.3 s −1 .…”
supporting
confidence: 60%
“…It is observed that η onset for Co 0.5 (V 0.5 ) is less than 250 mV, while the average overpotential required to achieve 10 mA cm −2 catalytic current density (η 10 ) is ≈300 mV (the best electrocatalyst in our case can achieve this at η 10 = 282 mV) ( Figure S13, Supporting Information), and the average current density that can be attained at an overpotential of 350 mV (J 350 ) is ≈42 mA cm −2 (54 mA cm −2 for the best electrocatalyst in our case). To make the comparison reasonable, electrocatalysts with carbon additives (e.g., carbon nanotubes and graphene) or porous substrates (e.g., Ni foam and carbon fiber paper) have been excluded from this list, owing to their "overestimated" geometric catalytic current density, as suggested by Stevens et al [19] Unexpectedly, Co 0.5 (V 0.5 ) is found to exhibit a significantly higher OER activity than most electrocatalysts in the list (Table S2, Supporting Information). Surprisingly, all the Co x (V 1−x ) samples, even without vanadium participation (i.e., Co 1 (V 0 )), are found to significantly outperform RuO 2 for OER (Figure 4a), demonstrating the advantage of this synthetic approach to obtain highly efficient electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The electrocatalytic kinetics was evaluated by the charge transfer property determined from the Nyquist plots . From the semicircles diameter in the low‐frequency zone, the charge transfer resistance ( R ct ) of the composites is shown in Figure d.…”
Section: Resultsmentioning
confidence: 61%